A spectromicroscopy study of the corrosion of polymer coated steel. (December 2018) - Situm, Arthur; Guo, Xiaoxuan; Barlow, Burke C.; Guo, Bao; Burgess, Ian J.; Grosvenor, Andrew P.
Highlights: A spectromiscropy method was developed to study corrosion of polymer-coated steel. Method allows for the study of corrosion of polymer-coated steel non-destructively. Corrosion was detected at steel-polymer interface without need of visual indicator. Studied ability of polymers to mitigate corrosion in high saline environments. Abstract: Methods for the study of corrosion of steel through opaque polymer films are limited and require the observation of surface defects to indicate corrosion. Reported herein is a novel methodology for the analysis of corrosion through a polymer film using a combination of X-ray fluorescence mapping (XRF) and micro X-ray absorption near-edge spectroscopy (μ-XANES). The method involves the comparison of XRF maps using an excitation energy that is just above the metallic Fe K-edge threshold (7115 eV). These XRF maps reveal a sharp contrast between corroded and non-corroded areas that can be confirmed by analysis of Fe K-edge μ-XANES spectra.